Thinking beyond the virus: perspective of patients on the quality of hospital care before and during the COVID-19 pandemic - Wong, Eliza Lai-yi; Wang, Kailu; Cheung, Annie Wai-ling; Graham, Chris; Yeoh, Eng-kiong (Frontiers in Public Health, 2023)
Objectives: The COVID-19 pandemic has a huge impact on the healthcare system and affects the normal delivery of routine healthcare services to hospitalised patients. This study aimed to examine the differences in patient experience of hospital service before and during COVID-19 among the discharged adult population. Methods: A territory-wide patient experience survey was conducted before and during COVID-19 (between October 2019 and April 2020) among patients discharged from the main acute and rehabilitation public hospitals in Hong Kong. A hierarchical ordinal logistic model was employed to examine the difference in multiple dimensions of patient experience, with adjustments of covariates. Results: In total, 9,800 participants were recruited. During the pandemic, there was a marginally significant increase in overall care rating (AOR: 1.12, 95% CI: 0.99-1.27), and an improvement in the timeliness of admission. However, significant reductions in patients’ confidence in nurses were observed. Communication of information regarding medication side effects reduced significantly (AOR: 0.72, 95% CI: 0.64-0.82). Conclusions: The patients hospitalised during the pandemic reported worse responsiveness in communication in their patient journey than those admitted before the pandemic. These findings will help develop appropriate strategies to address patients’ concerns in the new normal.